DEVELOPMENT TESTING METHOD AND ANALYSIS FOR STATIC THRUST MEASUREMENT - Khasyofi, Mitra
New aircraft development has to be supported with system development such as avionic, electric, structure and propulsion. Propulsion system is one of importance thing to influence aircraft performance. Propulsion system development either machine or propeller involved aircraft manufacturer and engine or propeller manufacturer that collaborated to perform test and evaluation. The main goal of this research was propulsion testing for unmanned aerial vehicle by evaluating thrust in static condition. Static thrust testing was conducted by force measurement using load cell and data acquisition systems. Thrust measurement result compared with analytic method and computer fluid dynamic simulation.